Characterization of a Yellow Laccase from Botrytis cinerea 241 - Ingrida Radveikienė; Regina Vidžiūnaitė; Rita Meškienė; Rolandas Meškys; Vida Časaitė (Journal of Fungi, 2021)
Typical laccases have four copper atoms, which form three different copper centers, of which the T1 copper is responsible for the blue color of the enzyme and gives it a characteristic absorbance around 610 nm. Several laccases have unusual spectral properties and are referred to as yellow or white laccases. Only two yellow laccases from the Ascomycota phylum have been described previously, and only one amino acid sequence of those enzymes is available. A yellow laccase Bcl1 from Botrytis cinerea strain 241 has been identified, purified and characterized in this work. The enzyme appears to be a dimer with a molecular mass of 186 kDa. The gene encoding the Bcl1 protein has been cloned, and the sequence analysis shows that the yellow laccase Bcl1 is phylogenetically distinct from other known yellow laccases. In addition, a comparison of amino acid sequences, and 3D modeling shows that the Bcl1 laccase lacks a conservative tyrosine, which is responsible for absorption quenching at 610 nm in another yellow asco-laccase from Sclerotinia sclerotiorum. High thermostability, high salt tolerance, broad substrate specificity, and the ability to decolorize dyes without the mediators suggest that the Bcl1 laccase is a potential enzyme for various industrial applications.